Effects of equine chorionic gonadotropin on progesterone-based estrus synchronization in Holstein Friesian × Brahman recipient cows - Jureerat Sumretprasong (2018)
Many estrous synchronization protocols have been developed to control the reproductive cycle in embryo transfer recipient cattle. Various breeds of cattle, such as Bos taurus, Bos indicus, or Bos taurus x Bos indicus respond to each protocol differently. The objective of this study was to seek an appropriate protocol for estrus synchronization in Holstein Friesian x Brahman crossbred recipients. Two synchronization protocols were tested: group 1) progesterone and prostaglandin (PG); and group 2) progesterone and PG plus equine chorionic gonadotropin (eCG). The addition of eCG reduced the time between progesterone withdrawal and appearance of estrous behavior from 60.8 ± 2.8 (mean ± SEM) h in group 1 to 31.5 ± 2.5 h in group 2 and improved synchronization (range 22-69 h in group 2 compared to 34-106 h in group 1). Furthermore, cows treated with eCG had better quality corpora lutea and more cows from this group were selected as recipients (62.8% versus 48%). The protocol using progesterone and PG plus 200 IU eCG in these crossbred cattle was more cost effective than the conventional protocol using progesterone and PG.